Study of surface plasmon resonance with zirconium oxide multilayer coatings of silver and gold films: reflection polarization modes and sensitivity - Sánchez Hernández, Héctor Hugo; Pérez Abarca, Juan Manuel; Sánchez Soto, Eduardo (Revista Mexicana de Fisica, 2024)
We propose a surface plasmon resonance (SPR) sensor based on multilayer films with silver (Ag) and gold (Au) interfaces coated with a thin layer of zirconium oxide (ZrO2) in Kretschmann configuration. A dielectric layer of ZrO2 acts as the prism coating and the second layer is deposited after the metal film in the dielectric/metal/dielectric (DMD) system. In order to achieve the best design for the sensor, the dependence of the sensitivity on the angle of incidence and the thickness of the alternating layer is comprehensively explored. The polarization change results are shown with the angles Ψ and ∆ which are the traditional ellipsometry measurement angles of the optical properties of the DMD system. The advantage of Ag/ZrO2 multilayers over Au and Au/ZrO2 for SPR refractive index detection in terms of sensitivity, as well as the Ag/ZrO2 interface offers the possibility of studies with promising features for SPR users to generalize this type of interface. The proposed DMD sensor is expected to find application in biochemical sensing due to its resolution.
Keywords: Resonancia de plasmones superficiales; Dieléctrico/metal/dieléctrico